Influence of temperature on ‘Rojo Brillante’ persimmon drying. Quality characteristics and drying kinetics - Cervera-Chiner, Lourdes; Vilhena, Nariane Q.; Larrea, Virginia; Moraga, Gemma; Salvador, Alejandra (Elsevier, 2024)
A physico-chemical characterization and drying kinetics study was performed for whole ‘Rojo Brillante’ persimmon subjected to hot-air drying at 35 ᵒC, 40 ᵒC and 45 ᵒC. Fruit was dried until a moisture content of 30 g water/100 g product, which is required to be considered dried persimmon. This moisture value was obtained after 12, 8 and 7 d when the drying process was applied at 35 ᵒC, 40 ᵒC and 45 ᵒC, respectively. All the drying treatments caused flesh structure changes, shrinkage and secondary epidermis formation. The final product's quality characteristics especially the texture, strongly depended on drying temperature. The fruit dried at 35 ᵒC exhibited a gelatinous internal texture and a thin secondary epidermis, similarly to that obtained during a natural drying process. The drying treatment at 40 ᵒC resulted in fruit having more rubbery flesh. However, the fruit dried at 45 ᵒC had a corky texture, with a very thick secondary epidermis that resulted in excessively tough fruit for commercialization purposes. The differences in flesh structure were revealed in the microstructural study by Cryo-FESEM. In all cases, soluble tannins content lowered to non-astringency values. Hot-air drying technology proved to be a good alternative to valorize discarded ‘Rojo Brillante’ persimmon.